25-(3x+5)=2(x+8)x

Simple and best practice solution for 25-(3x+5)=2(x+8)x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25-(3x+5)=2(x+8)x equation:



25-(3x+5)=2(x+8)x
We move all terms to the left:
25-(3x+5)-(2(x+8)x)=0
We get rid of parentheses
-3x-(2(x+8)x)-5+25=0
We calculate terms in parentheses: -(2(x+8)x), so:
2(x+8)x
We multiply parentheses
2x^2+16x
Back to the equation:
-(2x^2+16x)
We add all the numbers together, and all the variables
-3x-(2x^2+16x)+20=0
We get rid of parentheses
-2x^2-3x-16x+20=0
We add all the numbers together, and all the variables
-2x^2-19x+20=0
a = -2; b = -19; c = +20;
Δ = b2-4ac
Δ = -192-4·(-2)·20
Δ = 521
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-19)-\sqrt{521}}{2*-2}=\frac{19-\sqrt{521}}{-4} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-19)+\sqrt{521}}{2*-2}=\frac{19+\sqrt{521}}{-4} $

See similar equations:

| 8+6-y=10 | | -5(x+1)=-5 | | x+5=-12+7 | | 3x=9=-6 | | (2–7i)(9+5i)=0 | | 10.3=n+4.1 | | -3/11=k/6 | | 15=2-4z | | 7P+9=6p+15 | | (a-5)(3-2a)=0 | | x–5=–13 | | w-1=2 | | (X+6)(2x+6)=416 | | 43-99v=-11(9v-3) | | -20x+2x=2-8 | | 10x-2x=-4 | | 5.3(4x65+-2.6)=0 | | 4x=x^2=5 | | 5y+8=8(y-2) | | -3x+4x-2=10 | | 9u-4u=40 | | -3+4x-2=10 | | 78=18—5y | | 6x+9/13=2x-7 | | 0=-16t^2+33t+9 | | 4(a+2)=8+4=a | | 3x+4x=35x= | | x=2+3+3x10 | | 15=6w-1 | | |3x-12|+4x=2x-2 | | 6u+17=10u-19 | | (x+8)⋅(x+9)= |

Equations solver categories